The justice calling : where passion meets perseverance - Hoang, Bethany H., 1979-; Johnson, Kristen Deede; Labberton, Mark, 1953- (Grand Rapids, MI : Brazos Press, a division of Baker Publishing Group, 2016)
Offering a comprehensive biblical theology of justice drawn from the whole story of Scripture, this book invites us to know more intimately the God who loves justice and calls us to give our lives to seek the flourishing of others. The authors explore stories of injustice around the globe today and spur Christians to root their passion for justice in the persevering hope of Christ. They also offer practices that can further form us into people who join God's work of setting things right in the world.
Introduction: Justice and God -- Engage the whole story : justice and righteousness -- Receive God's vision of flourishing : justice and creation -- Move toward darkness : justice and the fall -- Lament : justice and Israel -- Live as saints (not heroes) : justice and Jesus -- Be sanctified and sent : justice and the church -- Persevere in hope : justice and all things being made new -- Conclusion: Abide in Jesus : justice and perseverance.
Includes bibliographical references (pages 205-216) and index.
Keywords: Christianity and justice; Social justice -- Religious aspects; Human trafficking -- Religious aspects; Rescue work -- Religious aspects; International Justice Mission